Empowerment across Cultures: How National Culture Affects Structural and Psychological Empowerment and Employee Engagement - Zheng, Miaoyun (Maria); Tian, Vane-Ing (Journal of Marketing Development and Competitiveness, 2019)
The importance of empowerment has grown in the past decades. Empowerment frees up management’s time from minor decision and can focus on broader strategies and the long-term objectives of the company. This paper aims to contribute empirically to the research of empowerment across cultures in manufacturing environment, focusing on how national culture dimensions affect structural and psychological empowerment and employee engagement. The data base on a practitioner’s model on sustainable engagement, in which both constructs of empowerment and sustainable engagement were surveyed and measured in a global manufacturing company for its group companies across more than 20 national cultures.